2012
DOI: 10.1074/jbc.m111.311605
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-dependent Corepressor (LCoR) Recruitment by Krüppel-like Factor 6 (KLF6) Regulates Expression of the Cyclin-dependent Kinase Inhibitor CDKN1A Gene

Abstract: Background: Ligand-dependent corepressor (LCoR) was identified as a repressor of nuclear hormone receptors. Results: A screen for new interacting factors revealed that LCoR acts with Krüppel-like factor 6 (KLF6) to repress CDKN1A gene transcription. Conclusion: KLF6 inhibits gene transcription by tethering a complex of proteins including LCoR to DNA. Significance: Identification of a novel mechanism of action of LCoR, independent of nuclear receptors, with potential implications for prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 48 publications
0
53
0
Order By: Relevance
“…Consistently, knockdown of klf6a decreased hepatocyte proliferation by upregulating cdkn1a in zebrafish (Zhao et al, 2010). Furthermore, it has been demonstrated that klf6 represses cdkn1a by a transcriptional co-repressor complex (Calderon et al, 2012). Because klf6 is known to be a transcriptional activator or repressor, it might play distinct roles depending on the developmental and tissue-specific contexts.…”
Section: Discussionmentioning
confidence: 78%
“…Consistently, knockdown of klf6a decreased hepatocyte proliferation by upregulating cdkn1a in zebrafish (Zhao et al, 2010). Furthermore, it has been demonstrated that klf6 represses cdkn1a by a transcriptional co-repressor complex (Calderon et al, 2012). Because klf6 is known to be a transcriptional activator or repressor, it might play distinct roles depending on the developmental and tissue-specific contexts.…”
Section: Discussionmentioning
confidence: 78%
“…Immunoprecipitations were performed as previously described (8). Samples were immunoprecipitated with α-IgG, α-HA (ab1424 or custom) or α-FLAG (F1804).…”
Section: Methodsmentioning
confidence: 99%
“…Knockdowns were performed essentially as previously described (8). Briefly, MCF-7/MCF10A/T47D cells were plated in 6-wells plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered expression profiles of KLF6 and its splice variants KLF6-SV1 have been observed in multiple cancer types. 1 Remarkable overexpression of KLF6-SV1, a dominant-negative spliced isoform with antagonistic function against KLF6-FL, has been identified in liver cancer, 16,21 lung cancer, 22 prostate cancer, 20,23,[42][43][44] breast cancer 24,[45][46][47] with reduced survival and unfavorable outcome. Conversely, siRNAmediated inhibition of KLF6-SV1 attenuated the cancer cell proliferation both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%